2019
DOI: 10.29271/jcpsp.2019.05.418
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of HLA-B*27 Subtypes in Patients with Ankylosing Spondylitis in Local Population

Abstract: Objective: To compare the distribution of HLA-B*27 subtypes in healthy controls and in ankylosing spondylitis (AS) patients of different ethnic groups from Pakistan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…10,11 Similarly, in a study on the Pakistani population by Lodhi et al, the HLA B2707 allele was more frequent in the healthy population in comparison to AS patients, whereas the B2706 allele was present only in the healthy group. 12 All these findings augment the results of the current study showing presence of HLA B27 more prevalent in healthy populations than in JIA patients, possibly due to the geographical distribution of the gene. In a study by Stanevicha et al, HLA B27 antigen was linked to JIA-ERA, oligoarthritis and polyarthritis.…”
Section: Discussionsupporting
confidence: 88%
“…10,11 Similarly, in a study on the Pakistani population by Lodhi et al, the HLA B2707 allele was more frequent in the healthy population in comparison to AS patients, whereas the B2706 allele was present only in the healthy group. 12 All these findings augment the results of the current study showing presence of HLA B27 more prevalent in healthy populations than in JIA patients, possibly due to the geographical distribution of the gene. In a study by Stanevicha et al, HLA B27 antigen was linked to JIA-ERA, oligoarthritis and polyarthritis.…”
Section: Discussionsupporting
confidence: 88%
“…In a Toronto cohort, HLA-B27 was one genetic marker associated with disease severity in PsA, but HLA antigens HLA-B39, and HLA=DQw3 were also associated with disease progression in the same cohort, while HLA-DR7 was "protective" (9) In the same cohort HLA-B39 was associated with progression in early disease (9). There are few population based data on HLA frequencies in SA, and particularly Pakistani, populations, though one small study suggested a low frequency (<3%) of the HLA-B27 genotype, and was a different sub-type (B*2707) (10). More recent genome wide studies have focussed more on susceptibility genes rather than disease severity genes.…”
Section: Discussionmentioning
confidence: 91%
“…The B* 2706 allele appears to have a protective role in the population studied because it was found in healthy controls. HLA-B*27:03 and 07 are the predominant subtypes in Punjabis and Pathans, respectively (3).…”
Section: Introductionmentioning
confidence: 99%